2005
DOI: 10.1128/aac.49.10.4288-4295.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Candida albicans Germ Tubes and Biofilms to Photofrin-Mediated Phototoxicity

Abstract: Treatment of mucocutaneous and cutaneous Candida albicans infections with photosensitizing agents and light, termed photodynamic therapy (PDT), offers an alternative to conventional treatments. Initial studies using the clinically approved photosensitizer Photofrin demonstrated the susceptibility of C. albicans to its photodynamic effects. In the present study, we have further refined parameters for Photofrin-mediated photodynamic action against C. albicans and examined whether mechanisms commonly used by micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
89
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 41 publications
6
89
0
4
Order By: Relevance
“…[17][18][19][20][21][22][23][24] The results of the present investigation demonstrated significant reduction of CFU/mL of C. albicans from tongues of mice after 400, 500, and 1000 mg/L of Photogem associated with LED light (305 J/cm 2 ) (455 and 630 nm). There is only one report describing a dose-dependent photoeradication of C. albicans in an immunodeficient murine model.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24] The results of the present investigation demonstrated significant reduction of CFU/mL of C. albicans from tongues of mice after 400, 500, and 1000 mg/L of Photogem associated with LED light (305 J/cm 2 ) (455 and 630 nm). There is only one report describing a dose-dependent photoeradication of C. albicans in an immunodeficient murine model.…”
Section: Discussionsupporting
confidence: 55%
“…A dose-dependent inhibition of metabolic activity was observed after treatment of C. albicans strains with Photofrin (0.01 to 10 mg/L) and illumination with a light fluence of 9 J/cm 2 from an Hg arc lamp. 20 Chabrier-Roselló et al 23 also observed a dose-dependent reduction of metabolic activity of C. albicans biofilms mediated by 10 mg/L of Photofrin and with broadbrand illumination by visible light at fluences ranging from 0.9 to 18 J/cm 2 . However, it has been shown that photosensitization of Candida and subsequent susceptibility to PDT can be reduced dramatically by culture conditions, such as the type of culture medium and the presence of albumin.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Besides the known fungicidal activity of APDI (7,11,24), we observed that sublethal photodynamic action had a temporarily fungistatic effect on C. albicans, and the extent of this activity was dependent on the amount of energy delivered to the cell-PS system, even under conditions bellow the photoinactivation threshold. The increase in lag phase observed immediately after APDI suggested that cell growth was arrested.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the generation of singlet oxygen is very sensitive to oxygen concentration, which may play a role in the photodynamic inactivation of bacteria comparable to that in eukaryotic cells (24). The experiments were carried out with Photofrin, one of the most widely used and clinically approved photosensitizers in photodynamic therapy, which also demonstrates antimicrobial efficacy (25)(26)(27).…”
mentioning
confidence: 99%